PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN PENERIMAAN DIRI SISWA KELAS X AK SMK LABOR BINAAN FKIP UNRI PEKANBARU T. A 2015/2016 - Sari, Wahyu Puspita; Umari, Tri; Arlizon, Raja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aim to find out studentâ€™s level of comprehension before conducting of the threatment by using guidance group service, to find out of the guidance group service process, to find out the comphrehension after conducting of the threatment by using guidance group service, the different of studentâ€™s compherehension between experiment group and contrl groupand the effect of guidance group service. The sample this research is class X AK SMK Labor Binaan FKIP UNRI Pekanbaru the total was 18 studentâ€™s. the result of this research is before conducting of guidance group service, the student category in the middle (100%) the process of guidance group service giving five time. After conducting guidance group service compherehension the category in the middle (67,5%) it mean that there was significant effect between studentâ€™s compherehension before and after conductingby using guidance group service. To find out the difference in experiment group and control group using Mann Whitney in SPSS with the result z = -2,266 with sig (2-tailed) was 0,023. The result sig (2-tailed) 0,023<0,005 it mean that â€œsignificant compherehension between experiment group and control groupâ€. Where as to contribution for service of guidance group service in student compherehension was 52%.Key Words :Guidance group service , self acceptance